GC-MS Analysis of Defensive Secretions of a Cuban Endemic Millipede of the Genus Rhinocricus—Chemical Prospecting of Neotropical Biodiversity - Juan Enrique Tacoronte Morales; Carla Bernal Villavicencio; Xavier Leopoldo Gracia Cervantes; Maria Elizabeth Canchingre; Maria Teresa Cabrera Pedroso (Chemistry Proceedings)
The poly-component composition of repugnatorial secretions isolated from Rhinocricus duvernoyi Kasrh 1981 eco-geographical populations, inhabiting in the eastern zone of Cuban archipelago, was analyzed using GC-MS. Were identified several benzoquinonoids and related derivatives, revealing the existence of a singular compositional heterogeneity at a geographical scale. The preliminary molecular-geographic mapping of the Cuban archipelago detailed the presence of 3 chemotypes in the east region. The work reports a structural-chromatographic molecular database containing the components of defensive secretions.